Impact of Annual Budgets in Economic Development of Nepal: An Econometric Analysis - Sharma, Om (Economic Literature, 2016)
This paper deals with the impact of the annual budgets on the economic development process of Nepal. The epoch-making macro economic variables are introduced through the application of the econometric models of various kinds, such as linear, log-linear in single equation system, multiple forms and the Granger Causality test (1969) by applying the annual data for the period of 1974/75 to 2006/07 in current as well as constant term. The high average elasticity coefficient of manufactured GDP, GDP, GNP and PCI respectively indicate that development expenditure is highly significant in determining development. A nominal role of internal borrowing and internal revenue in the economy and the excessive dependence on foreign aid has led the country for heavy debt service obligations every years forcing for additional tax burden.Economic Literature, Vol. XI (1-14), June 2013